(untitled) (Baghdad Science Journal, 2011)
This study is conducted to investigate the validity of using different levels of Rustumiya sewage water for irrigation and their effects on corn growth and some of the chemical properties of the soil such as electrical conductivity and soil pH in extract soil paste , the micro nutrient content in soil and plant which are ( Fe , Mn , Zn , Cu , Cd , Pb ). Three levels of sewage water ( 0 , 50 , 100 )% in two stages were used ,the three levels of wastewater ( without soil fertilization ) were used in the first stage , Where 80 Kg N /D+50Kg P2O5 /D was added to the soil as fertilizer in the control (0%) treatment and 40 Kg N/D+25Kg P2O5/D were added to 50 and 100% levels in the second stage .Corn seeds were planted in 12kg plastic pots in Completely Randomized Block Design in three replicates . The results show a high significant increase in plant height , fresh and dry weight for all treatments in comparison with control treatment . The low added level of sewagewater in both stages gave a significant increase of plant height and fresh and dry weight . The results showed a high increased of electrical conductivity for 50 , 100% wastewater added levels for both stages compared with control treatment , The high added level 100% gave high significant increase in electrical conductivity compared with the low level of the sewagewater .Whereas the values of soil PHwere close to the neutral for all treatment.The results showed a significant increase in micro nutrients content ( which include Fe , Mn , Zn , Cu , Cd , Pb ) in soil and plant for all treatments compared with control treatment . This increase was continued with the increase of additional level of sewagewater . However all the micro nutrient were within the allowable natural limits and not reached the toxic limits in soil and plant .